Electronic transformer performance evaluation and its impact on PMU. Issue 23 (7th November 2019) - Li, Jue; Liu, Hao; Martin, Kenneth E.; Li, Jinsong; Bi, Tianshu; Yang, Qixun
Abstract : The electronic transformer of smart substations, which transfers primary signals, is important for measurements and controls. In this study, the transformation characteristics of a Rogowski electronic current transformer (ECT) are analysed theoretically. Then, experimental platforms are established to verify the analysis and study the impact of the transformation characteristics of the ECT and an electronic voltage transformer (EVT) on a phasor measurement unit (PMU) using standard test signals. The analysis and the testing results show that this ECT can transfer the phasor well under both steady and dynamic conditions. However, the harmonics introduced by the ECT may lead to the measurement errors of frequency and the rate of the change of the frequency (ROCOF) from the PMU. Therefore, a phasor algorithm with powerful DC offset and harmonics immunity is suggested for PMUs connected to the output of this type of ECT. For the EVT, the ROCOF measurements are easily affected as well. The EVT was also shown to be more sensitive to temperature than the potential transformer (PT).